KONDISI SOSIAL EKONOMI DAN PERAWATAN YANG DIINGINKAN PENDUDUK LANJUT USIA - Sukamdi Sukamdi; Umi Listyaningsih; Faturochman Faturochman (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2000)
The number of elderly in the province of Yogyakarta Special Region has showed an absolute and relative tendencies to increase. The average increase from 1971 to 1995 which was 3.27 percent per year, cannot be separated from the uprising of people life expectancy. The increasing of life expectancy, in one hand indicates to be positive phenomena, but in another hand, brings forth the problem of cares. The changes of time and family structures have affected the cares of aging people which was different from what they did to their parents. This study which applies both qualitative and quantitative methods in the subdistricts of Umbulharjo, Kraton, and Pakualaman, within the city of Yogyakarta shows that the majority of elderly has disapproved the presence of special institutions for them. To take care of aging persons has been regarded as an obligation of every children to indicate devotions to their parents. Furthermore, for elderly living with children and grandchildren, may also serve as motivation of life enthusiasms and to keep away from loneliness as the most troublesome psychological problems.